2010
DOI: 10.2225/vol13-issue4-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Variety discrimination of Tigridia pavonia (L.f.) DC. assesed by different length RAPD primers

Abstract: Financial support:We are grateful to Consejo Nacional de Ciencia y Tecnología (CONACYT) from México for the scholarship give to JLPE , and to the RED TIGRIDIA (SINAREFI, México) for covering the publishing payment.Keywords: genetic resources, RAPD, Tigridia pavonia, variety discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…According to this, it is possible that the GC content favored the major efficiency of the 15-(65% GC) and 20-base primers (60% GC) that were used in this study because more DNA fragments were amplified and also a greater percentage of polymorphism was detected (92.7 and 98.5, respectively) compared with those that were amplified with 10-base primers, which had 72% GC content and 80% polymorphism ( Table 2). Our results are similar to those that were reported by Solouki et al (2008) and Piña-Escutia et al (2010b), where more DNA fragments and 100% polymorphism were obtained using a long primer with low GC content.…”
Section: Rapd Markerssupporting
confidence: 92%
“…According to this, it is possible that the GC content favored the major efficiency of the 15-(65% GC) and 20-base primers (60% GC) that were used in this study because more DNA fragments were amplified and also a greater percentage of polymorphism was detected (92.7 and 98.5, respectively) compared with those that were amplified with 10-base primers, which had 72% GC content and 80% polymorphism ( Table 2). Our results are similar to those that were reported by Solouki et al (2008) and Piña-Escutia et al (2010b), where more DNA fragments and 100% polymorphism were obtained using a long primer with low GC content.…”
Section: Rapd Markerssupporting
confidence: 92%
“…Forty-three accessions from Korea and 23 accessions from China were successfully distinguished from each other using just four of 14 SSR markers, providing a simple approach for discriminating between Korean and Chinese sesame accessions. Piña-Escutia et al (2010) used 10-, 15-, or 20-base primers to discriminate between nine varieties of Tigridia pavonia (L.f.) DC in Mexico. The authors found that a long primer (20 bases) generated a similar dendrogram to those constructed using shorter primers, with the exception of a single variety whose placement shifted as a result of using a longer primer.…”
Section: Discussionmentioning
confidence: 99%